Examining determinants of book-tax difference: Insights from Malaysian multinational corporations - Nordin, Nurliyana; Hamid, Nadiah Abd; Rasit, Zarinah Abdul; Razak, Fairuz Abd; Mohamad, Azlinda Binti (Journal of Ecohumanism, 2024)
This research investigates the factors affecting the book-tax differences of multinational corporations (MNCs) operating in Malaysia. The sample for this study consists of MNCs with subsidiaries in tax haven countries listed on the Financial Times Stock Exchange (FTSE) Bursa Malaysia Kuala Lumpur Composite Index (KLCI) and FTSE Bursa Malaysia Mid 70 Index. About 67 MNCs were selected after eliminating 32 companies with inadequate data and one with extreme outliers. A secondary data approach was employed, utilising multiple regression analysis. Selected corporate characteristics, including deferred tax liabilities and assets, taxable income, interest coverage ratio, return on assets, and effective tax rate, were used as independent variables. Descriptive analysis revealed evidence that corporations with a high return on assets (ROA) typically benefit from very high levels of book-tax differences (BTDs). Furthermore, the results indicate that a high interest coverage ratio may partly explain the outcomes leading to an increase in differences recorded between book income and taxable income. Thus, this supports the idea that a positive relationship exists between the interest coverage ratio and BTD. Hence, this study contributes to the tax literature and informs policymakers on factors influencing BTD, especially MNCs with subsidiaries in tax haven countries. The study aims to contribute to the existing body of knowledge by offering insights into the factors influencing MNCs’ strategic tax planning decisions in the Malaysian context. Policymakers should address the unfair allocation of the worldwide tax base, where a reasonable portion of the earnings made by MNCs doing business in a nation should be subject to taxation in that nation.